Metamorphic evolution of relict lawsonite‐bearing eclogites from the (U) HP metamorphic belt in the Chinese southwestern Tianshan. (29th March 2014) - Du, J. X.; Zhang, L. F.; Bader, T.; Chen, Z. Y.; Lü, Z.
Abstract In the Chinese southwestern Tianshan (U)HP belt, former lawsonite presence has been predicted for many (U)HP metamorphic eclogites, but only a very few lawsonite grains have been found so far. We discovered armoured lawsonite relicts included in quartz, which, on its part, is enclosed in porphyroblastic garnet in an epidote eclogite H711‐14 and a paragonite eclogite H711‐29. H711‐14 is mainly composed of garnet, omphacite, epidote and titanite, with minor quartz, paragonite and secondary barroisite and glaucophane. Coarse‐grained titanite occasionally occurs in millimetre‐wide veins in equilibrium with epidote and omphacite, and relict rutile is only preserved as inclusions in matrix titanite and garnet. H711‐29 shows the mineral assemblage of garnet, omphacite, glaucophane, paragonite, quartz, dolomite, rutile and minor epidote. Dolomite and rutile are commonly rimed by secondary calcite and titanite respectively. Porphyroblastic garnet in both eclogites is compositionally zoned and exhibits an inclusion‐rich core overgrown by an inclusion‐poor rim. Phase equilibria modelling predicts that garnet cores formed at the P‐peak (490–505 °C and 23–25.5 kbar) and coexisted with the lawsonite eclogite facies assemblage of omphacite + glaucophane + lawsonite + quartz. Garnet rims (550–570 °C and ~20 kbar) grew subsequently during a post‐peak epidote eclogite facies metamorphism and coexisted with omphacite + quartz ± glaucophane ± epidote ± paragonite. The results confirm the former presence of a cold subduction zone environment in the Chinese southwestern Tianshan. The P–T evolution of the eclogites is characterized by a clockwise P–T path with a heating stage during early exhumation (thermal relaxation). The preservation of lawsonite in these eclogites is attributed to isolation from the matrix by quartz and rigid garnet, which should be considered as a new type of lawsonite preservation in eclogites. The complete rutile–titanite transition in H711‐14 took place in the epidote eclogite facies stage in the presence of an extremely CO2‐poor fluid with X(CO2) [CO2/(CO2 + H2O) in the fluid] <<0.008. In contrast, the incomplete rutile–titanite transition in H711‐29 may have occurred after the epidote eclogite facies stage and the presence of dolomite reflects a higher X(CO2) (>0.01) in the coexisting fluid at the epidote eclogite facies stage.